Mechanistic pathway of NP-polymer interface to engender nanoscale confinement. (June 2022) - Wang, Guotong; Wang, Ruijie; Wang, Chengyuan; Tang, Chun; Luo, Ying; Xiao, Dunhui
Abstract: Nanoparticle (NP)-polymer interface imposes the confinement effects on the surrounding polymer, which in turn impacts the bulk properties of nanocomposites. This study aims to identify the physical origin of the nanoscale confinement and reveal the pathway of the NP-polymer interface to produce the confinement effects. Herein, molecular dynamics simulations and theoretical analyses show clear evidence that the interfacial interaction generates a high compression in the polymer, which lead to an increased mass density and the upshift of glass transition temperature. This eventually triggers the redistribution of the polymer density partially via the orientation adjustment of the polymer chain segments. Graphical abstract: Image 1 Highlights: The confinement effects originate from the interfacial interaction. The interfacial interaction generates a high compression in the polymer. This compressive stress leads to the physical changes in the polymer. The external loadings may change the confinement effects.